The Experience of Newly Formed Syrian Female-Headed Households Refugees in Egypt: Challenges and Opportunities - Dia, Wasim (AUC Knowledge Fountain, 2026)
This thesis examines the lived experience of Newly Formed Syrian Female-Headed Households in Egypt. It focuses on how the extended displacement reshapes gender roles, decision-making, and survival strategies. Since the beginning of the Syrian conflict in 2011, extensive family separation, death, disappearance, and male migration have occurred, leading to a significant rise in female-headed Syrian refugee households. As a result, displacement has intensified women’s vulnerability, generating new responsibilities and limited spaces for agency, especially within restrictive legal and socio-economic environments. Based on in-depth qualitative interviews conducted in 2023, this research explores how Syrian refugee women navigate everyday life in Egypt without spousal support. It analyzes how gender intersects with caregiving responsibilities, livelihood constraints, social networks, and legal status to shape women’s experiences in exile. This study draws on intersectionality theory and migration network theory to examine how structural inequalities and social ties simultaneously constrain and enable women’s actions. The findings show that displacement not only eliminated traditional gender roles but also reconfigured them. Women assumed new dual roles as primary breadwinners and caregivers, often engaging in informal and unstable work while managing household survival. These shifts intensified women’s emotional and physical strain and limited yet meaningful forms of empowerment, including decision-making power and financial autonomy. However, these gains remained constrained by a restrictive legal framework, social stigma, and limited access to services. By examining the lived realities of Syrian female-headed households in Egypt, this study contributes to the feminist migration scholarship by offering insights into constrained forms of agency and highlighting the limitations of existing humanitarian and policy responses.